Upaya Dosen Tahsin Al-Qiraah dalam Meningkatkan Kemampuan Membaca Al-Quran Mahasiswa Jurusan Syari’ah Institut Agama Islam Negeri Curup - Febriyarni, Busra (STAIN Curup, 2018)
This paper is intended to examine and describe tahsin al-qiraah activities, constraints and efforts of lecturers to succeed the activity. For this reason, teaching staff must strive to create students who are qualified in the field of Islam. In this case it must start from the basic course of reading Al-Quran or tahsin al-qiraah. what efforts were made by the Al-Qiraah doctoral lecturer to improve the Qoran reading ability of Sharia majors. This type of research was field research, with a qualitative descriptive approach. The results of this study indicate that the ability to read the Qoran to Syari'ah IAIN Curup students relatively was still classified as medium, with a count of 50% had been able to read well, and 50% again needed intensive and programmed guidance. The causes of factors were less able to read the Qoran for Curup IAIN Syari'ah students, including previous student educational background, process selection of students at the time of admission of new students who do not pay attention to the standard of reading the Qoran for prospective students of IAIN Curup, Family factors that pay less attention to read Al-Quran seriously lazy to learn to read the Qoran. Efforts to improve and improve students' ability to read al-Quran include IAIN policies, uniform material, lecturer, curriculum, media, and other facilities such as rooms and learning resources.